The Various Methods to Prevent Lithium Toxicity in Treatment for Patients with Bipolar Disorder - Sriram, Diksha; Liao, Clara (Journal of Student Research, 2023)
Bipolar disorder (BD) is a serious mental illness that leads to considerable shifts in mood, energy, and physical activity levels, impairing a person’s ability to complete day-to-day tasks. About 4.4% of adults in the US report having experienced an episode of BD at least once in their life, and approximately 82.9% of people with BD are left severely impaired. To combat this, doctors prescribe lithium, which is an effective mood stabilizer that can regulate the extreme highs and lows of BD. However, lithium is a toxic substance when it exceeds the therapeutic range, requiring frequent trips to the hospital to evaluate blood lithium levels Such monitoring may not always be effectively feasible, especially for patients experiencing a mental health crisis or patients in rural areas without local medical facilities. Research studies have been conducted to provide patients with alternative methods to avoid lithium toxicity including ways to check the lithium levels on their own Additionally, studies investigate the ideal dosing regimen to prevent toxic side effects, while others aim to prevent toxicity before it happens.